Building trust among muslim donors on Islamic social finance crowdfunding platforms: the role of financial disclosure and social presence - Frank Aligarh; Didik Prasetyanto; Bayu Sindhu Raharja; Anissa Hakim Purwantini; Vela Retna Widyastuti (Journal of Islamic Accounting and Finance Research, 2026)
Purpose - This study aims to address this gap by integrating the Stimulus-Organism-Response (SOR) framework to examine the determinants of the intention to donate on crowdfunding platforms, with a particular focus on financial disclosure and social presence. Method - This research employed both online and direct face-to-face survey methods for data collection. A total of 282 respondents from various regions across Indonesia were successfully obtained for data analysis. To predict the model, Structural Equation Modeling-Partial Least Squares (SEM-PLS) was employed to evaluate both the inner and outer models. Result - The research findings indicate that stimulus factors, such as financial disclosure, can serve as key predictors of trust and reputation. Meanwhile, social presence also positively influences trust, empathy, and reputation. Organizational factors, including trust, empathy, and reputation, have been shown to motivate individuals to donate through crowdfunding platforms. As a result, all the proposed hypotheses are supported. Implication - The study highlights the need for crowdfunding platforms to continuously improve financial transparency to sustain trust and reputation, while also encouraging traditional philanthropic organizations to adopt technology that enhances transparency and accountability. Originality - This study offers novelty by introducing financial disclosure as a key stimulus in the Stimulus–Organism–Response (SOR) framework to explain donation intention on crowdfunding platforms. It also extends prior research by demonstrating how financial transparency and social presence simultaneously shape donors’ trust, empathy, and perceived platform reputation in the context of donation-based crowdfunding in Indonesia.